2021
DOI: 10.3390/biomedicines9101299
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy for EGFR Mutation Analysis in Advanced Non-Small-Cell Lung Cancer Patients: Thoughts Drawn from a Real-Life Experience

Abstract: Background: Liquid biopsy analysis for EGFR detection in cell-free DNA (cfDNA) from NSCLC patients has become routine. The aim of this study was to explore its applicability in clinical practice. Methods: We collected data of EGFR-mutated NSCLC patients with liquid biopsy analysis. Data included test timing, concomitant tissue re-biopsy, therapy change, histology, stage, smoking habits, gender and age. All analyses were performed via a real-time PCR method to analyze EGFR mutations at exons 18, 19, 20 and 21. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Lung cancer (LC) is the main cause of cancer-related death worldwide [ 1 ]. Non-Small Cell Lung Cancer (NSCLC), the most common LC histology, is a heterogeneous malignancy comprising molecular subtypes for which targeted agents are available in clinical practice [ 2 ]. Epidermal Growth Factor Receptor ( EGFR ) is the most common altered targetable gene in NSCLC, and its mutations (mainly exon 19 deletions and exon 21 L8585R mutations) represent the predictive biomarker for first-, second- and third-generation EGFR -Tyrosine Kinase Inhibitors (TKIs).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer (LC) is the main cause of cancer-related death worldwide [ 1 ]. Non-Small Cell Lung Cancer (NSCLC), the most common LC histology, is a heterogeneous malignancy comprising molecular subtypes for which targeted agents are available in clinical practice [ 2 ]. Epidermal Growth Factor Receptor ( EGFR ) is the most common altered targetable gene in NSCLC, and its mutations (mainly exon 19 deletions and exon 21 L8585R mutations) represent the predictive biomarker for first-, second- and third-generation EGFR -Tyrosine Kinase Inhibitors (TKIs).…”
Section: Introductionmentioning
confidence: 99%
“…Although the development of gene detection technology is changing with each passing day, most of the rare mutations in the clinic cannot be identified. At present, some studies have found that 49 liquid biopsy analysis can be used as an alternative method for EGFR detection in tumor tissues, for patients with positive or negative EGFR in tumor biopsies, but most of the fluid biopsy analysis in this study was carried out in patients with advanced NSCLC during TKI treatment, and its clinical application needs to be further improved. One urgent task is to develop and use gene detection methods that can more accurately identify different rare EGFR mutations as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, liquid biopsies enable the tracking of minimally recurrent illness, treatment efficacy, and the detection of clonal evolution or the establishment of resistance mutations. Additionally, studying ctDNA and CTCs in cases of haematological malignancies offers hope for disease monitoring and relapse prediction [ 76 , 77 ].…”
Section: Reviewmentioning
confidence: 99%